(untitled) (New Delhi, 1999)
This book is writen with the conscious aim of generating a more informed public debate on the nuclear issue and providing a useful input into the making of India's policies beyond Pokhran II.
Keywords: Nuclear weapons,Vũ khí hạt nhân; India,Ấn Độ